PERANCANGAN APLIKASI PENGOLAHAN DATA BUKU DAN PENGUNJUNG PERPUSTAKAAN PADA TAMAN BACAAN MASYARAKAT AR-RASYID ACEH BESAR - Munawar Munawar; Mira Maisura; Chairan M Nur (UIN Ar-Raniry, 2019)
This research is motivated by several places or educational institutions that still use manual methods in processing books, members' data, visits and loans that are less effective and time consuming. TBM Ar-Rasyid in the process of filling in the guest book, and data collection on books, loans, members are still done manually. So that a lot of energy and resources will be wasted, both in terms of material and in terms of time, this research is conducted to build a data processing system that can be used by library staff in data collection of books, members, visits and loans to be easier and more effective. The research method used is R & D and for system development using the waterfall method. Then after testing the system, namely in the form of black box testing and continued with the user acceptance test (User Acceptend Test) to users, namely members, library officers, the test results obtained with an average value of 4.31 with a percentage of 86% which means it is very suitable or very easy. Users feel satisfied with the system built.